GPCRs overexpression and impaired fMLP-induced functions in neutrophils from chronic kidney disease patients - Scharf, Pablo; Sandri, Silvana; Rizzetto, Felipe; Xavier, Luana Filippi; Grosso, Daniela; Correia-Silva, Rebeca D.; Farsky, Pedro S.; Gil, Cristiane D.; Farsky, Sandra Helena Poliselli (Frontiers in Immunology, 2024)
G-protein coupled receptors (GPCRs) expressed on neutrophils regulate their mobilization from the bone marrow into the blood, their half-live in the circulation, and their pro-and anti-inflammatory activities during inflammation. Chronic kidney disease (CKD) is associated with systemic inflammatory responses, and neutrophilia is a hallmark of CKD onset and progression. Nonetheless, the role of neutrophils in CKD is currently unclear. Herein, blood and renal tissue were collected from non-dialysis CKD (grade 3 -5) patients to evaluate GPCR neutrophil expressions and functions in CKD development. CKD patients presented a higher blood neutrophil-to-lymphocyte ratio (NLR), which was inversely correlated with the glomerular filtration rate (eGFR). A higher frequency of neutrophils expressing the senescent GPCR receptor (CXCR4) and activation markers (CD18 + CD11b + CD62L + ) was detected in CKD patients. Moreover, CKD neutrophils expressed higher amounts of GPCR formyl peptide receptors (FPR) 1 and 2, known as neutrophil pro-and antiinflammatory receptors, respectively. Cytoskeletal organization, migration, and production of reactive oxygen species (ROS) by CKD neutrophils were impaired in response to the FPR1 agonist (fMLP), despite the higher expression of FPR1. In addition, CKD neutrophils presented enhanced intracellular, but reduced membrane expression of the protein Annexin A1 (AnxA1), and an impaired ability to secrete it into the extracellular compartment. Secreted and phosphorylated AnxA1 is a recognized ligand of FPR2, pivotal in anti-inflammatory and efferocytosis effects. CKD renal tissue presented a low number of neutrophils, which were AnxA1 + . Together, these data highlight that CKD neutrophils overexpress GPCRs, which may contribute to an unbalanced aging process in the circulation, migration into inflamed tissues, and efferocytosis.